THE INFLUENCE OF SOCIAL MEDIA ON MENTAL HEALTH AND WELLNESS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article examines the influence of social media on mental health and well-being. It discusses the potential negative effects such as comparison and self-esteem issues, fear of missing out (FOMO), cyberbullying and harassment, sleep disturbances, and social isolation. The article emphasizes the importance of maintaining a healthy balance between social media use and well-being and suggests strategies for achieving this balance. By understanding the potential pitfalls of excessive social media use, individuals can prioritize their mental health and well-being while still benefiting from virtual connections.